Adsorptive Removal of Malachite Green Dye onto Coal-Associated Soil and Conditions Optimization - T. R. Sundararaman; A. Saravanan; P. Senthil Kumar; M. Millicent Mabel; R. V. Hemavathy; S. Karishma; S. Jeevanantham; R. Hemavathi; A. Ishwariya; S. Kowsalya (Adsorption Science & Technology)
The present research was investigated to eliminate the cationic dye (malachite green (MG)) from the water environment using coal-associated soil. The adsorbent material was characterized using scanning electron microscopy (SEM) and Fourier Transform Infrared Spectrophotometer (FTIR) analyses. Batch experiments were performed to investigate the different factors which affect the adsorption study. The maximum percentage removal of MG dye was attained as follows: adsorbent dose of 1.0 g/L (0.2 to 1.6 g/L), solution pH of 6.0 (2.0 to 9.0), temperature of 30°C (30 to 60°C), time contact of 60min (10 to 90 min), and dye’s concentration of 25 mg/L (25 to 150 mg/L). The adsorption isotherm was studied with four different isotherm models and results showed that the Freundlich isotherm model gave the best fit than the other nonlinear models to designate the isotherm behaviours with R2 value of 0.9568, and the maximum adsorption capacity of coal-associated soil for MG dye adsorption is 89.97 mg/g. The evaluation of kinetic studies was performed by using three different kinetic models, where it exposed that pseudofirst order providing the best fit with R2 value of 0.96 (25 to 150 mg/L). The thermodynamic parameters Gibbs free energy (ΔG°), entropy (ΔS°), and enthalpy (ΔH°) were endorsing that the present adsorption system was exothermic. Thus, the experimental results state that coal-associated soil could be an alternative material for the exclusion of dyes from water.